2006
DOI: 10.1007/s00216-006-0466-6
|View full text |Cite
|
Sign up to set email alerts
|

Determination of complex mixtures of volatile organic compounds in ambient air: canister methodology

Abstract: Canister methodology is applicable to 150 polar and nonpolar VOCs found in ambient air from parts-per-billion by volume (ppbv) to parts-per-million (ppmv) levels, and has been validated at parts-per-trillion (pptv) levels for a subset of these analytes. This article is a detailed review of techniques related to the collection of volatile organic compounds (VOCs) in evacuated Summa and fused-silica-lined canisters, and their analysis by gas chromatography/mass spectrometry (GC/MS). Emphasis is placed on caniste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 73 publications
0
40
0
Order By: Relevance
“…We speculate that these compounds formed abiotically due to the high levels of ammonia, 2,3-butanedione, and 3-hydroxy-2-butanone present since these compounds peak levels were coordinated with presence of 3-hydroxy-2-butanone. Previous research has shown that pyrazines form under mild conditions in presence of the aforementioned compounds (Shu and Lawrence, 1995;Shu, 1998;Yaylayan and Haffenden, 2003) with tertramethylpyrazine being its main product (Yaylayan and Haffenden, 2003), and with the addition of formaldehyde both di-and trimethyl oxazoles form as well (Wang and Austin, 2006). These compounds have low odor thresholds and may be responsible for some of the pungent and oppressive odors associated with poultry production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that these compounds formed abiotically due to the high levels of ammonia, 2,3-butanedione, and 3-hydroxy-2-butanone present since these compounds peak levels were coordinated with presence of 3-hydroxy-2-butanone. Previous research has shown that pyrazines form under mild conditions in presence of the aforementioned compounds (Shu and Lawrence, 1995;Shu, 1998;Yaylayan and Haffenden, 2003) with tertramethylpyrazine being its main product (Yaylayan and Haffenden, 2003), and with the addition of formaldehyde both di-and trimethyl oxazoles form as well (Wang and Austin, 2006). These compounds have low odor thresholds and may be responsible for some of the pungent and oppressive odors associated with poultry production.…”
Section: Resultsmentioning
confidence: 99%
“…However, slow filling of canisters and sampling in humid environments can result in condensation of water at the sample container inlet and inside canisters both of which can lead to potential loss of compounds (McClenny et al, 1999;Wang and Austin, 2006). It has also been shown that certain polar compounds associated with AFOs do not lend themselves to canister analysis (Koziel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although electropolished stainless steel canisters or bags made of inert materials can also be used to store air samples (e.g. Apel et al, 1999;Janson et al, 1999;Plass-Dülmer et al, 2006;Wang and Austin, 2006) with the advantage that no adsorption/desorption steps are needed, they are not commonly used for field BVOC measurements due to their high cost, extra precautions needed to avoid leaks, difficulties in evaluation of compound losses during storage, and problems in coupling canisters to open gas-exchange systems, especially for replicate measurements (for possible caveats see Apel et al, 1999;Batterman et al, 1998;Plass-Dülmer et al, 2006;Wang and Austin, 2006).…”
Section: Problems Of Sampling and Calculation Of Emission Ratesmentioning
confidence: 99%
“…We used an Entech 7200 preconcentrator and 7016D autosampler to concentrate samples and introduce them to a gas chromatograph (GC) system for analysis. We used cold trap dehydration to reduce water vapor in the sample, as described by Wang and Austin (2006). The GC system consisted of two Shimadzu GC-2010 GCs with a flame ionization detector (FID) and a Shimadzu QP2010 Mass Spectrometer (MS), respectively.…”
Section: Flux Chambermentioning
confidence: 99%